Finlandiya’da Türkoloji eğitimi - Bauer, Özge (My University, 2024)
Bu çalışmanın amacı Finlandiya’daki Türkoloji eğitiminin ve çalışmalarının ortaya çıkma sebeplerini incelemek ve bu doğrultuda verilen eserleri tespit etmektir. Finlandiya`da Türkoloji eğitiminin başlamasındaki en etkili faktör Hegel`in görüşlerine dayandırılan dil kavramı üzerinden ulus olma bilincine giden yoldaki kültürel ve siyasi dönüşümdür. Daha sonra da dilin kökenine dair yapılan araştırmalarda geliştirilen Ural-Altay dil hipotezidir. Finlandiya ile Türkiye’nin tarihsel seyrine baktığımızda bütün Avrupa’yı etkileyen siyasal ve kültürel dalgalanmaların özellikle de 1800’lerde benzer şekilde gerçekleştiği görülmektedir. 1800’lerde Fin dil bilimcilerin Fin diliyle ilgili yaptıkları çalışmaları Türkoloji çalışmalarına önemli katkılar sağlamıştır. Hegel`in, Herder`in, Humboldt`un görüşleri de siyasi, kültürel, edebi açıdan intikal etmiştir. Bu nedenle Fin dil bilimciler Fin halkını ulus yapabilmek için bilimsel araştırmalar yapmışlardır. Kültürel olarak dönüşümü sağlayan en önemli unsur da dildir. Bu nedenle Fin dili ile ilgili olan sorular Fin bilimcileri keşiflere sürüklemiş ve Doğu bilimi çalışmalarıyla bağlantılı olarak da Türkoloji çalışmalarına katkı sağlayacak önemli eserlere imza atılmıştır. Araştırma kapsamında bir ana, altı alt problemin sorularına yanıt aranmıştır. Bu sorular doğrultusunda Finlandiya’da dünya çapında Türkoloji çalışmalarına etki eden akademisyenlerin kimler olduğu, Türkçeyi niçin ve nasıl öğrendikleri, kitap, kitap bölümü, makale, yüksek lisans ve kapsamında hangi çalışmaların yapıldığı araştırılmıştır. Fince, İngilizce, Almanca olmak üzere kaynak dildeki metinler üzerinden yazılan bu tezin Türkiyat araştırmalarına katkı sağlayacağı düşünülmektedir.

The aim of this study is to examine the factors underlying the emergence of Turkology education and research in Finland, and to identify the relevant scholarly works. The most influential factor in the establishment of Turkology education in Finland is the cultural and political transformation towards national consciousness, driven by the concept of language rooted in Hegelian philosophy. Subsequently, the Ural-Altaic language hypothesis, which emerged from research on the origins of language, further contributed to this development. When examining the historical trajectories of Finland and Turkey, it becomes evident that the political and cultural transformations affecting Europe, particularly in the 19th century, unfolded in a similar manner in both countries. In this period, Finnish linguists' research on the Finnish language made significant contributions to the development of Turkology. The views of Hegel, Herder, and Humboldt exerted significant political, cultural, and literary influence. Consequently, Finnish linguists undertook scientific research aimed at fostering a sense of national identity among the Finnish people. Language, as the primary driver of cultural transformation, played a crucial role in this process. As a result, inquiries into the Finnish language led these scholars to produce substantial works, many of which contributed to Turkology, in connection with the broader field of Oriental studies. This research seeks to address one primary research question and six secondary questions. In alignment with these inquiries, the study examines which academicians in Finland have contributed to the development of Turkology on a global scale, the reasons and methods behind their acquisition of the Turkish language, and the scope of their scholarly output, including books, book chapters, articles, and master's and doctoral theses. This thesis, based on texts in the source languages of Finnish, English, and German, is expected to make a significant contribution to Turkic studies.
Turkology studies in Finland
Keywords: Education of Turkology; Fin Dili; Fin-Ugor Dilleri; Finland; Finlandiya; Finlandiya`da Türkoloji Çalışmaları; Finnish Language; Finno-Ugric languages; Öğrenim ve öğretim; Study and teaching; Turkish language; Turkology Studies in Finland; Türk dili; Türkoloji Eğitimi